Origin of salt in Antarctic saline lake waters through trace element analysis - Masuda, Noriyasu; Nakaya, Shyu; Torii, Tetsuya (1984)
P(論文) The origin of trace elements in Antarctic saline lake waters is still not clear. Waters of five Antarctic saline lake and ponds in the Wright Valley and the Taylor Valley, and one coastal glacier ice were analyzed by the neutron activation method. Three possible origins, connate sea water, rock weathering and tropospheric aerosol particle, were investigated. The correlations of chemical constituents between the South Pole aerosol particle and the lake and pond waters indicate that trace elements in the Antarctic saline lake and pond waters might have been derived mostly from aerosol particles. departmental bulletin paper